Ordinance No. 1: Protecting Public Morality, Order and Safety, undated, reprinted in Ordinances of the Town of Bedford 2 (1869) - (:unkn) unknown (My University, 1869)
§ 4: Prohibited the concealed carry of any dirk, pistol, Bowie-knife, dagger, sword in cane, or any other dangerous or deadly weapon concealed. Also prohibited carrying weapons with intent of injuring another. Violators fined not more than ten dollars.
Keywords: CARRY - CONCEALED; CARRY - INTENT TO COMMIT CRIME